(untitled) (Agricultural Engineering, 2018)
The objective of the paper was to determine the impact of the shearing speed and cultivator tines flexibility on the vertical forces value. The study was carried out in field conditions in sandy clay soil and the average moisture of 11.2%. The vertical forces acting on four “s” tines with flexibility of 0.0061; 0.0711; 0.0953 and 0.1406 m∙kN−1 were measured. Tines were ended with a cultivator point with the curvature radius of 0.17 m. Measurements were made for four shearing speeds (1.0; 1.7; 2.4 and 3.0 m·s−1) and the shearing depth of 11 cm. A stand for measurement of forces acting on soil shearing farm tools in field conditions was used. It was concluded that the shearing speed caused a linear increase of the vertical force but the growth gradient does not depend on the tines flexibility. It was also concluded that the increase in flexibility causes an initial increase and then decrease of the vertical force, which was described with the second degree parabola equation. Flexibilities, at which extremes of courses occur, grow along with the reduction of the shearing speed.